Controls of depositional facies patterns on a modern carbonate platform: Insight from hydrodynamic modeling. (14th February 2019) - Purkis, Sam J.; Harris, Paul (Mitch); Cavalcante, Georgenes
Abstract: Recent studies of Holocene deposits on Great Bahama Bank (GBB) have focused on mapping of sediment distribution, an analysis of the variable filling of accommodation space, a comparison between ooid sandbodies and an examination of whitings and mud production. Collectively, these studies provide insight into the variability in depositional facies that challenge outcrop and subsurface interpretations. Missing from these analyses, however, has been a scrutiny of the physical controls over deposition. To partially explore these controls, a hydrodynamic model forced by prevailing ocean hydrodynamics, tides, winds and atmospheric pressure was developed. Current intensity and direction can be examined at short time steps over 1 year, and GBB can be partitioned into zones of mean annual hydrodynamic energy. Areas of vigorous tidal exchange correspond to localities where platform margin ooid sand shoals have developed. There is a predictive relationship between increasing peak current velocity and increasing area of the sandbody for the Cat, Joulter and Schooners Cays and Tongue of the Ocean sites. A connection between platform‐top hydrodynamics and the formation/suppression of whitings is evidenced west of Andros, suggesting a relationship between the production/deposition of platform‐top muds and off‐platform circulation. Filling of accommodation space can be partially related to platform topography and hydrodynamic flow. For instance, accommodation filling occurs locally along the platform margin by grainstones in areas of high tidal exchange as well as by mud accumulation leeward of islands. Conversely, the development of hiatal surfaces (sites of non‐deposition) occurs in areas not sheltered by islands, such as the southern GBB, where platform‐top currents are persistently vigorous. A broader understanding of platform‐top currents and their diverse controls can aid interpretation of the rock record, including the type and distribution of platform‐top sediments, the distribution of hiatal surfaces and, therefore, identification of locations which have the potential to host more complete depositional cycles. Abstract : Recent studies of Holocene Great Bahama Bank have not focused on the physical controls over sediment deposition, which is the topic of this manuscript. To explore these controls, a hydrodynamic model forced by prevailing ocean hydrodynamics, tides, winds and atmospheric pressure was developed. Our results may provide even more robust quantitative comparative sedimentology and stratigraphy guidelines.